Clinical application: Restoration of immune homeostasis by autophagy as a potential therapeutic target in sepsis - ZHANG, LEMENG (Exp Ther Med, 2016)
Sepsis-induced lymphocyte and dendritic cell apoptosis contributes to immunosuppression, resulting in an inability to eradicate the primary infection and a propensity to acquire secondary infections. However, the inhibition of apoptosis may produce unexpected and undesirable consequences. Another cellular process, autophagy, is also activated in immune cells. There is increasing evidence to suggest that autophagy confers a protective effect in sepsis. The protective mechanisms underlying this effect include limiting apoptotic cell death and maintaining cellular homeostasis. Therefore, understanding the regulation of immune cell autophagy and apoptosis may provide insight into novel therapeutic strategies. The present review examined potential novel therapeutic strategies aimed at restoring immune homeostasis by inducing autophagy. The restoration of balance between apoptosis and autophagy may be a novel approach for improving sepsis-induced immunosuppression and decreasing susceptibility to sepsis.